Targeted vaccination campaigns of teenagers after two clusters of B invasive meningococcal disease in Brittany, France, 2017 - Pivette, Mathilde (BMC Public Health, 2020)
BACKGROUND: In December 2016, three cases of serogroup B invasive meningococcal disease, including two children from the same middle school (11 to 15 years old pupils), occurred in the department (administrative district) Côtes-d’Armor (Brittany, France). They were infected by a rare strain (B:P1.7–2,4:F5–9:cc162), covered by the 4CMenB vaccine (Bexsero®). Four months later, two cases due to the same strain occurred in a high school in the same area (15 to 19 years old students). In accordance with French recommendations, vaccination was proposed to students of both schools and to all individuals aged 11–19 years living or studying in the hyperendemic area. We describe these vaccination campaigns, from the alert to the impact evaluation. METHODS: The target population included 8884 people: 579 in the middle school, 2007 in the high school and 6298 in the community. In both schools, vaccination sessions were organized directly on site. In the community, teenagers were vaccinated by general practitioners. The vaccination campaign took place from May to October 2017. An active pharmacovigilance follow-up was set up to document adverse effects of the vaccine. RESULTS: Considering the whole target population, the vaccination coverage was estimated at 43% for 1 dose and 34% for 2 doses. Higher vaccination coverage was observed in the schools (79% in the middle school and 42% in the high school for 2 doses) than in the community (27% for 2 doses). The reported adverse effects were consistent with the safety profile of the vaccine and no severe adverse effect was reported. CONCLUSIONS: This vaccination campaign was the third one implemented with Bexsero® in France and constitutes a reproducible approach for future targeted vaccination campaigns. No additional cases of the same strain have occurred since the end of the campaigns in the area.